2012
DOI: 10.2174/1877382601003010030
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy: Understanding Pathologic Angiogenesis and Exploring its Treatment Options

Abstract: Diabetic retinopathy is the major cause of blindness at working age. The pathogenesis behind visual loss is related with retinal angiogenesis and increased retinal vascular permeability. These changes seem to be the result of chronic hyperglycemia and hypoxia. Several mechanisms have been proposed to cause the retinal and vasculature cellular damage. They include the formation of advanced end glycation products, aldose reductase activity and reactive oxygen species. Ultimately, they lead to the expression of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…These side effects also occur with intraocular formulations and may additionally limit their application. Currently, several different steroids are being used to treat DME, namely, triamcinolone, fluocinolone, and dexamethasone [ 49 51 ].…”
Section: Inflammatory Mediators and Medical Treatmentmentioning
confidence: 99%
“…These side effects also occur with intraocular formulations and may additionally limit their application. Currently, several different steroids are being used to treat DME, namely, triamcinolone, fluocinolone, and dexamethasone [ 49 51 ].…”
Section: Inflammatory Mediators and Medical Treatmentmentioning
confidence: 99%
“…The physiopathology of diabetic retinopathy (DR) and DMO is complex and still not well understood [ 22 ]. High levels of VEGF-A have been identified in the retina and vitreous of patients with DMO and DR [ 23 ]. This signal protein increases vascular permeability and progression from non-proliferative diabetic retinopathy (NPDR) to proliferative diabetic retinopathy (PDR) [ 23 , 24 ].…”
Section: Diabetic Retinopathy and Macular Oedemamentioning
confidence: 99%
“…High levels of VEGF-A have been identified in the retina and vitreous of patients with DMO and DR [ 23 ]. This signal protein increases vascular permeability and progression from non-proliferative diabetic retinopathy (NPDR) to proliferative diabetic retinopathy (PDR) [ 23 , 24 ]. Anti-VEGF drugs can successfully inhibit this protein and prevent the aforementioned consequences.…”
Section: Diabetic Retinopathy and Macular Oedemamentioning
confidence: 99%
“…11 The examined patients were above 40 years old. A study conducted in the United States of America 12 found that diabetic patients aged above 40 years old have higher prevalence of getting DR which would threaten their eyesight. This study shows that the highest number of patients with DR is dominated by patients aged 50-59 years old while patients above 60 years old are fewer.…”
Section: Discussionmentioning
confidence: 99%